2017
DOI: 10.1097/md.0000000000006641
|View full text |Cite
|
Sign up to set email alerts
|

Influence of occupation and education level on breast cancer stage at diagnosis, and treatment options in China

Abstract: The objective of this study was to evaluate the impact of occupation and education level of Chinese female breast cancer patients on their cancer staging at diagnosis, clinical and pathological features, rate of implementation, and selection of treatment.The medical charts of 4211 confirmed female breast cancer cases diagnosed between 1999 and 2008, from 7 breast cancer centers spread across the whole of China, were reviewed. Data including information on the patient's sociodemographic status, clinical and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 40 publications
5
43
1
3
Order By: Relevance
“…Greater educational attainment is believed to equip individuals with sufficient cognitive skills, personal control, and economic resources to drive them to pursue a preventive healthy lifestyle [35], and in turn, would have the impact to avert the grueling morbidity associated with treatment. Lower education has been shown to be closely related to advanced-staged BC [36], affecting thereby treatment choices. Similarly, a disease with aggressive features is more often detected by clinical breast examination than by self-detection [37]; practicing of the latter inculcates health alertness and well correlates with tertiary education [38] and younger age [39].…”
Section: Discussionmentioning
confidence: 99%
“…Greater educational attainment is believed to equip individuals with sufficient cognitive skills, personal control, and economic resources to drive them to pursue a preventive healthy lifestyle [35], and in turn, would have the impact to avert the grueling morbidity associated with treatment. Lower education has been shown to be closely related to advanced-staged BC [36], affecting thereby treatment choices. Similarly, a disease with aggressive features is more often detected by clinical breast examination than by self-detection [37]; practicing of the latter inculcates health alertness and well correlates with tertiary education [38] and younger age [39].…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] After statistical adjustment of other sociodemographic factors in the current study, race was no longer found to be a significant prognostic factor, a finding that is consistent with the results of a previous population-based study. In addition, patients with lower socioeconomic status 23,24 and a lower educational level 25 were more likely to delay office visits and had tumors of higher stages at the time of diagnosis. Income and medical insurance often indicate a patient's financial ability to afford the expensive cost and long course of myeloma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…20 The poor financial affordability could dramatically prevent patients from receiving optimal treatments. In addition, patients with lower socioeconomic status 23,24 and a lower educational level 25 were more likely to delay office visits and had tumors of higher stages at the time of diagnosis. Malnutrition in impoverished patients also could make the adverse effects of myeloma treatment intolerable and prevent physicians from prescribing aggressive therapy, 26 a situation that also was observed in patients with complicated comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the higher the level of a person's education, the higher possibility not to be late in searching for health services. Yang Liu et al (2017) women who have lower levels of education were likely to have poorer quality of life. People with low education usually live in areas far from urban and technological advancements in which one is difficult to be exposed to the possibility of early breast cancer screening so that the risk of delay in the search for health services and the diagnosis of breast cancer is higher in women with lower levels of education.…”
Section: Predisposing Factors With Health Service Search Behaviormentioning
confidence: 99%
“…This is reinforced by data shown by Yang Liu, Jian Zhang, Rong Huang, We-Liang Feng, Ya-Nan Kong et al (2017), where it is estimated that about 15% of deaths in women in the world are caused by breast cancer. Not only in the world level, Indonesia also has a high incidence of breast cancer (Yang Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%